Effect of phytosanitary products used on cassava crop on biological aspects of entomopathogenic fungi (Research, Society and Development, 2020)
This study aimed to evaluate the interaction of commercial phytosanitary products registered or in the process of registration for use in cassava crop, on biological aspects of Beauveria bassiana and Metarhizium anisopliae under laboratory conditions. The products tested were Actara®, Callisto®, Cypermethrin®, Curryon®, Fusilade®, Gaucho®, Nomolt®, Poquer®, Standark Top® and Tiger®, and their action was evaluated on the germination parameters, colony forming unit (CFU), vegetative growth and conidium production. The data obtained from the different biological parameters were analyzed, and the compatibility between the products and the fungi was based on the calculation of toxicity proposed by biological index. There was a differentiated response of the fungi in relation to the products tested, B. bassiana was compatible with all except Fusilade®. For M. anisopliae the products Gaucho®, Poquer® and Cipermetrina® were considered moderately toxic, while the other products were compatible.